2020
DOI: 10.1021/acsami.0c14679
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Electrochemical Impedance Detection of Mycoplasma agalactiae DNA by Low-Cost and Disposable Au-Decorated NiO Nanowall Electrodes

Abstract: Nanostructured electrodes detecting bacteria or viruses through DNA hybridization represent a promising method, which may be useful in on-field applications where PCR-based methods are very expensive, time-consuming, and require trained personnel. Indeed, electrochemical sensors combine disposability, fast response, high sensitivity, and portability. Here, a low-cost and high-surface-area electrode, based on Au-decorated NiO nanowalls, demonstrates a highly sensitive PCR-free detection of a real sample of Myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…15 ). This mechanism, similar to the one at the base of DNA hybridization sensors, contributed to the R ct increase 62 .…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…15 ). This mechanism, similar to the one at the base of DNA hybridization sensors, contributed to the R ct increase 62 .…”
Section: Resultsmentioning
confidence: 59%
“…The fit of the EIS spectrum based on an equivalent circuit model allows the determination of the circuit parameters. By monitoring these parameters, EIS can be used to sensitively detect impedance variations at the electrolyte/electrode interface caused by the adsorption of molecules or particles 62 .…”
Section: Resultsmentioning
confidence: 99%
“…The changes to the phase angle were not signicant. 78 Bode phase angle plots provide further information for the characterization of conductive materials, such as supercapacitors 19 and sensors. 14 For example, the capacitor response frequency (f 0 ) is characterized as the position of equal resistive and capacitive impedance, 20 and the relaxation time constant (s 0 ) which is dened as the minimum time for discharging all energy from a device that has an efficiency larger than 50%.…”
Section: Bode Plotsmentioning
confidence: 99%
“…As a result, they showed that this type of electrode can detect DNA in the concentration range from 10 fmol/L to 1 nmol/L. Another DNA EIS-sensor was recently proposed in ref 139, where the authors have used an Au-decorated NiO nanowall electrode covered by DNA from Mycoplasma agalactiae. Unlike the previously discussed DNA sensor, this device demonstrates efficiency over a range of relatively high DNA concentrations (0.2−1.5 μmol/L), which nevertheless allows it to be used for fast, accurate, and inexpensive detection of Mycoplasma agalactiae in sheep milk.…”
Section: Eis Applications In Biology and Medicinementioning
confidence: 99%